Parasite fauna of rodents (Murinae) from El Hierro (Canary Islands, Spain): A multidisciplinary approach - Feliu, Carlos; López, Mercedes; Gómez, María S.; Torres, Jordi; Sánchez, Santiago; Miquel, Jordi; Abreu-Acosta, Néstor; Segovia, Juan M.; Martín-Alonso, Aarón; Montoliu, Isabel; Villa, Mercedes; Fernández-Álvarez, Ángela; et al. (Acta Parasitologica, 2012)
The parasite fauna (protozoa, helminths and insects) of the two most widespread Murinae rodents in El Hierro (Canary Islands, Spain), the black rat () and the house mouse () was studied. Faunistic, ecological, ecotoxicological data, as well as information on the biology of some nematode parasites of are provided. The present work is unprecedented in the Canary Islands, and provides the first data on the parasite biodiversity in Murinae from the archipelago. Concerning to parasitofaunas stands out: a) impoverishment of biodiversity of helminths respect of which have the same hosts in other islands; b) increasing the number of species of Siphonaptera, even compared with flea species that parasitize the same hosts from continental biotopes. 178 171 0,506 1,0 Q3 Q4 SCIE